Produção de sentidos numa charge contemporânea uma análise dialógico-discursiva - Wilder Kleber Fernandes de Santana; Sra. Edlaine; Sr. Junior (Revista Odisséia, 2022)
This paper discusses the word as a discursive and ideological phenomenon in social interactions. To reflect on this issue, we have as a general objective to carry out a theoretical-methodological discussions of the word under a discursive perspective, whose support is based on the assumptions of the Bakhtin (2006, 2008, 2019), Volóchinov (2017), Medviédev (2016) and adjacent, like Brait (2006, 2013), Faraco (2009) and others. The methodology of this research followed a qualitative approach of interpretative nature (MINAYO, 2001; SILVEIRA & CÓRDOVA, 2009), based on the research proposal in line with the Dialogic Discourse Analysis, which is supported by the postulates of Bakhtin Circle thinking. The analysis is based on a contemporary cartoon published in digital media by Jota Camelo. The results show that when taken into account the ideological meanings that surround the discursive production, the word takes on an amplitude that crosses structural boundaries and thickens in the responsive character of the constitution of the subject of language.